On the Dark Side: Conrad's "The Secret Sharer" and Valenzuela's "La palabra asesino" - Donald L. Shaw (Studies in 20th & 21st Century Literature, 2008)
Conrad’s famous “The Secret Sharer” and the short story “La palabra asesino” [“The Word ‘Killer’” in its English translation] by the Argentine Luisa Valenzuela both concern psychological self-exploration and self-discovery, through contact with a killer, a situation which challenges conventional moral standards. It is suggested that a comparison between the two stories may throw reciprocal light on both of them. In each story an act or acts of murder becomes a trigger which sets off a train of psychological events, somewhat different in the two cases. Discussion of the differences highlights the authors' priorities and the significance they attach to the darker side of the human personality. Both stories are highly ambiguous; but the ambiguity serves a different purpose in each case. Conrad is concerned with psychological "doubling"; Valenzuela with exploration of aspects of the human personality which in turn may be related to aspects of Argentina's collective personality as it expressed itself during the “Dirty War.” An examination of the different forces in play in the two stories improves our understanding of both.
Keywords: Conrad; The Secret Sharer; Valenzuela; La palabra asesino; human personality; murder; Dirty War; Argentina; ambiguity